One-stage tracheostomy during surgery reduced early pulmonary infection and mechanical ventilation length in complete CSCI patients - Sun, Lin; Feng, Haoyu; Mei, Jun; Wang, Zhiqiang; Deng, Chen; Qin, Zhixin; Lv, Junqiao (Frontiers in Surgery, 2023)
Objective Complete cervical spinal cord injury (CSCI) is a devastating injury that usually requires surgical treatment. Tracheostomy is an important supportive therapy for these patients. To evaluate the effectiveness of early one-stage tracheostomy during surgery compared with necessary tracheostomy after surgery, and to identify clinical factors for one-stage tracheostomy during surgery in complete cervical spinal cord injury. Design Data from 41 patients with complete CSCI treated with surgery were retrospectively analyzed. Participants and interventions Ten patients (24.4%) underwent one-stage tracheostomy during surgery, thirteen (31.7%) underwent tracheostomy when necessary after surgery, and eighteen (43.9%) did not have a tracheostomy. Main results One-stage tracheostomy during surgery significantly reduced the development of pneumonia at 7 days after tracheostomy (p = 0.025), increased the PaO2 (p < 0.05), and decreased the length of mechanical ventilation (p = 0.005), length of stay (LOS) in the intensive care unit (ICU) (p = 0.002), hospital LOS (p = 0.01) and hospitalization expenses compared with necessary tracheostomy after surgery (p = 0.037). A high neurological level of injury (NLI) (NLI C5 and above), a high PaCO2 in the blood gas analysis before tracheostomy, severe breathing difficulty, and excessive pulmonary secretions were the statistically significant factors for one-stage tracheostomy during surgery in the complete CSCI patients, but no independent clinical factor was found. Conclusions In conclusion, one-stage tracheostomy during surgery reduced the number of early pulmonary infections and the length of mechanical ventilation, ICU LOS, hospital LOS and hospitalization expenses, and one-stage tracheostomy should be considered when managing complete CSCI patients by surgical treatment.